OPTIMASI KARBOPOL DAN HPMC DALAM FORMULASI GEL ANTIJERAWAT NANOPARTIKEL EKSTRAK DAUN SIRIH (Piper betle Linn) - Dwi Saryanti; Dian Nugraheni; Nisa Sindi Astuti; Natasya Intania Pertiwi (Jurnal Ilmiah Manuntung, 2019)
Gel is a semisolid preparation that is clear, translucent containing active ingredients, can provide a cool effect on the skin and good spread of the skin. The use of gelling agent in gel formulations greatly affects the physical properties of the resulting gel preparations. HPMC is a gel forming material that is neutral and can form a clear gel and can maintain the viscosity of the resulting gel, while carbopol are easily dispersed in water and produce preparations with sufficient viscosity. The research conducted aims to determine the comparison of carbopol and HPMC in the optimal gel formula of betel leaf extract nanoparticles with Simplex Lattice Design method. The response used was pH, viscosity, spreadability, adhesion and antibacterial activity against Staphylococcus aureus. The results obtained by carbopol concentration of 80.9% and HPMC 19.1% was the optimal gel formula of betel leaf extract nanoparticle. Based on the verification, an insignificant difference was obtained between the predictions of the software and the results of the tests performed. This shows that the method used was valid or can be trusted.